A columnar liquid crystal with permanent polar order. Issue 5 (12th January 2015) - Guilleme, J.; Aragó, J.; Ortí, E.; Cavero, E.; Sierra, T.; Ortega, J.; Folcia, C. L.; Etxebarria, J.; González-Rodríguez, D.; Torres, T.
Abstract : The self-assembly of axial dipolar subphthalocyanine molecules in the presence of electric fields leads to uniaxially oriented columnar liquid crystalline materials that exhibit permanent polarization. Abstract : The self-assembly of axial dipolar subphthalocyanine molecules in the presence of electric fields leads to uniaxially oriented columnar liquid crystalline materials that exhibit permanent polarization.